Microbiology - Sharma, Dushyant Kumar (Alpha Science International Ltd., 2013)
MICROBIOLOGY is the study of microorganisms - organisms which are too small to be seen with unaided eyes. They are present everywhere in our environment. They act both as our friend and foe. They include bacteria, fungi, virus, protozoa and algae. The book deals with various aspects of microorganisms - diversity of microbial life, their physiology and genetics, importance of microorganisms to mankind, methods to control them and tools and techniques to study them. It not only focuses on the fundamentals but also covers the application aspect of the subject. The book will help the readers to explore and understand the fascinating world of microorganisms.